INTERNALISASI NILAI-NILAI TOLERANSI DALAM MEMBENTUK KARAKTER INKLUSIF PADA SISWA SEKOLAH MENENGAH ATAS NEGERI 4 PROBOLINGGO - Hasanatul Karimah; Maskuri Bakri; Imam Syafi’i (VICRATINA, 2022)
Indonesia is a country whose people have a lot of diversity, and with this diversity it is hoped that they can be tolerant of each other. A person can be tolerant of each other because of the instillation of values in him. In the world of education, the cultivation of values must also be carried out on all students to avoid discriminatory attitudes between students, because this attitude can lead to disputes and hostility resulting in divisions. SMA Negeri 4 Probolinggo is one of the schools that instill values of tolerance in forming an inclusive character in students. This research is a case study research, using observation research methods, unstructured interviews, and documentation. The results of this study are the values of tolerance that are instilled in students including the value of tolerance for mutual respect, respect, accepting diversity, being open to change, and avoiding discrimination. The value investment is carried out in 3 stages, namely; 1) value transformation stage, 2) value transaction, and 3) value transinternalization. In the process of inculcating these values, the teacher uses a model of cultivating dogmatic values by using a personality approach, exemplary methods, and habituation strategies.